2023
DOI: 10.3389/fphys.2023.1137063
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of skeletal stem/progenitor cells in distinct skeletal compartments

Abstract: Skeletal stem/progenitor cells (SSPCs), characterized by self-renewal and multipotency, are essential for skeletal development, bone remodeling, and bone repair. These cells have traditionally been known to reside within the bone marrow, but recent studies have identified the presence of distinct SSPC populations in other skeletal compartments such as the growth plate, periosteum, and calvarial sutures. Differences in the cellular and matrix environment of distinct SSPC populations are believed to regulate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 181 publications
0
4
0
Order By: Relevance
“…In the 1980s, Owen and Friedenstein proposed using lineage tracing with genetic markers to verify the stem cell nature of marrow resident osteogenic precursors. As anticipated, this approach successfully identified several candidate skeletal stem/progenitor cell (SSPC) populations, including Nestin + [ 20 ] and LepR + [ 21 ] cells, while more recent studies combining lineage tracing with single cell RNA-based sequencing identified additional SSPCs in bone marrow, the growth plate, the periosteum, and calvarial sutures [ 22 ]. It is also well established that SSPCs resident in bone marrow secrete cytokines/chemokines that govern the retention and maintenance of HSCs [ 23 ].…”
Section: Fibroblast Colony-forming Cells (Fcfcs) Colony-forming Unit-...mentioning
confidence: 99%
“…In the 1980s, Owen and Friedenstein proposed using lineage tracing with genetic markers to verify the stem cell nature of marrow resident osteogenic precursors. As anticipated, this approach successfully identified several candidate skeletal stem/progenitor cell (SSPC) populations, including Nestin + [ 20 ] and LepR + [ 21 ] cells, while more recent studies combining lineage tracing with single cell RNA-based sequencing identified additional SSPCs in bone marrow, the growth plate, the periosteum, and calvarial sutures [ 22 ]. It is also well established that SSPCs resident in bone marrow secrete cytokines/chemokines that govern the retention and maintenance of HSCs [ 23 ].…”
Section: Fibroblast Colony-forming Cells (Fcfcs) Colony-forming Unit-...mentioning
confidence: 99%
“…Osteogenesis, the process of bone development and formation, is crucial to maintain the skeletal system [ 15 ]. Osteogenesis is involved in the process of bone remodeling and the subsequent repair of bone fractures [ 16 , 17 ]. Osteogenesis is tightly regulated by mechanical and biochemical signaling pathways [ 18 ].…”
Section: Osteogenesis and The Differentiation Of Osteoblast Lineage C...mentioning
confidence: 99%
“…Osteogenesis is tightly regulated by mechanical and biochemical signaling pathways [ 18 ]. During osteogenesis, the sequential differentiation occurs in osteoblast lineage cells, including mesenchymal stem cells (MSCs), osteoprogenitors, pre-osteoblasts, osteoblasts, and osteocytes [ 16 , 17 , 19 , 20 , 21 , 22 ]. Osteoblasts secrete the organic matrix osteoid, which is subsequently calcified to form the bone.…”
Section: Osteogenesis and The Differentiation Of Osteoblast Lineage C...mentioning
confidence: 99%
“…[46] This suggests that Prrx1 + cells are important in tooth development and represent a dental stem/progenitor population, similar to Prrx1 + stem cells present in the long bone periosteum and calvarial suture. [47][48][49] Lastly, αSMA-green fluorescent protein (GFP) transgenic mice showed the presence of GFP + cells in the molar and incisor dental pulp from P7 to 6 weeks of age. These cells express Sca1 (a MSC marker) and are involved in odontogenesis during growth and development.…”
Section: Current In Vivo Approaches To Study Dpscs In Pulp Regenerationmentioning
confidence: 99%